The Development of a Digital Module on the Concept and Application of the Kurikulum Merdeka in Madrasas Based on Problem-Based Learning - Naifah; Zuhrudin, Ahmad; Alfurochmatin, Anisa; Lathifah, Winda Nur; Mudrofin (Institut Agama Islam Negeri Curup, 2025)
This study aimed to develop and evaluate a digital module entitled Concept and Application of the Kurikulum Merdeka in Madrasas to address the lack of accessible references and limited research on relevant teaching materials. These gaps have contributed to students' perceptions of the Manāhij Ta‘līm al-Lughah al-‘Arabiyah fi al-Madāris course as outdated and impractical. Grounded in the Problem-Based Learning (PBL) approach, the study employed the ADDIE model—Analyze, Design, Develop, Implement, and Evaluate—as its development framework. A total of 110 respondents participated in the needs analysis, 27 in the implementation phase, and 64 in the practicality testing. Data were collected through questionnaires, interviews, observations, documentation, and tests. Expert validation indicated high feasibility, with scores of 96% from subject-matter experts and 90% from media design experts. Student responses also reflected strong acceptance, with a practicality rating of 93.7%, indicating high user satisfaction and ease of use. The module significantly enhanced learning outcomes, as demonstrated by an increase in average scores from 56.89 (pretest) to 87.41 (posttest), with a paired-sample t-test confirming statistical significance, t(26) = -169.56, p < .001. These results suggest that the digital module is both pedagogically robust and practically effective in supporting Arabic language instruction in madrasas within the Kurikulum Merdeka framework.